Qualité de l’insertion socioprofessionnelle de nouveaux travailleurs et travailleuses diplômés: Examen d’un schéma exploratoire - Fournier, Geneviève; Jeanrie, Chantale; Croteau, Line (Canadian Journal of Higher Education, 1999)
Since the issues related to socioprofessional integration extend well over objective facts of reality and are also influenced subjective facts of one’s reality, it is important to identify those facts that allow prediction of the quality of the socioprofessional integration of new workers. The objective of this article is to present an exploratory schéma gathering three types of variables defining quality of socioprofessional integration and three other types of variables that are likely to predict this quality. This schéma was tested with a subsample of 97 new workers, all graduated from higher education programmes. Results from regression analyses have enlighted the relative strength of some objective and subjective criteria and show that all the schéma ’s variables except age contribute to the understanding of socioprofessional integration of young graduated. Three major findings came out from the analyses: the low predictive value of demographic variables, the marked preponderance of the variable "role of job market’s characteristics in the attainment of one’s goals" in predicting professional integration quality and, finally, the predictive importance of the link between job and school training.